PENGARUH PERTUMBUHAN UJRAH DAN INVESTASI TERHADAP PERTUMBUHAN ASET PADA PERUSAHAAN ASURANSI JIWA DI INDONESIA - Rustamunadi Rustamunadi; Aas Asmawati (Syar'Insurance: Jurnal Asuransi Syariah, 2019)
Abstract Assets are assets owned by the company. High asset growth shows that the company can optimize its assets well. High asset growth can increase public trust in the company. One of the factors affecting the assets of Islamic life insurance companies is contribution and claims. Problem formulation in this research are: 1) How does the influence of the growth of ujrah on the growth of assets in Islamic life insurance companies? 2) What is the effect of investment growth on the growth of sharia life insurance company assets? 3) How does the simultaneous growth of ujrah and investment affect the growth of sharia life insurance company assets? This study aims to examine: 1) To analyze the effect of the growth of the ujrah on the growth of assets in the Sharia Life Insurance company. 2) To analyze the effect of investment growth on asset growth in Islamic Life Insurance companies. 3) To analyze the effect of simultaneous growth in investment and investment on asset growth in Sharia Life Insurance companies. The analysis used is multiple linear regression analysis, where in this method to determine the effect of the growth of ujrah and investment on the growth of assets displayed in the form of a regression equation. Tests used in this study are classic assumption tests including: normality test, heteroscedasticity test, multicollinearity test and autocorrelation test. In this study the authors used secondary data samples from the financial statements of 6 Islamic life insurance companies in Indonesia. Based on the Ujrah growth test, it has a sig value of 0.525> 0.05 and a tcount value of 0.643> ttable 2.03693, therefore it can be concluded that the growth of the ujrah (X1) partially has no significant effect on asset growth. While investment growth has a sig value of 0.006 <0.05 and tcount 2.932> t table 2.03452, therefore it can be concluded that investment growth (X2) has a significant negative effect on asset growth. Based on the F test of ujrah growth and investment has a sig value of 0.022 <0.05, the growth of ujrah and investment has a simultaneous effect on the growth of assets and growth of assets influenced by the growth of ujrah and investment growth of 15.9% and 84.1% influenced by other variables not discussed in this study.